Meditative practices for stress reduction the well-being as competence of health proffessionals - Reboiras, Fabiana; Grzona, Esteban (Revista del Hospital Italiano de Buenos Aires, 2015)
Meditative practices are part of the oriental culture and recently western world has started to explore their benefits in health sciences. This article tries to explain in scientific terms topics that were discussed before from religious and spiritual conceptions. Researches about meditative practices influence on stress reduction are rising. The aim of this article is perform a hybrid approach between science findings and author’s meditative experience. It shows recent results about mechanisms and benefits of meditative practices in healthy people and patients with different pathologies: neurophysiological changes, psychophysical pain relief, emotional regulation, improvements in social life and life satisfaction. Finally, the article introduces potential contributions of these practices on wellness and stress reduction in medical students and health professionals
Keywords: mindfulness; meditation; stress reduction; medical education; health professionals; wellness